2007
DOI: 10.1029/2006gl029223
|View full text |Cite
|
Sign up to set email alerts
|

Ring current at Saturn: Energetic particle pressure in Saturn's equatorial magnetosphere measured with Cassini/MIMI

Abstract: [1] The Magnetospheric Imaging Instrument (MIMI) on the Cassini spacecraft provides measurements of the energetic ion population within the magnetosphere of Saturn. Energetic ion directional intensities, energy spectra and ion composition, are measured by the Charge Energy Mass Spectrometer (CHEMS) over the range $3 to 236 keV per charge and by the Low Energy Magnetospheric Measurements System (LEMMS) for ions in the range 0.024 < E < 18 MeV. This work reports preliminary results of partial particle pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 17 publications
14
116
0
Order By: Relevance
“…The plasma beta measured by the spacecraft for these crossings ranged between 15 and 25 and was exceptional compared to previous studies by Sergis et al [2007Sergis et al [ , 2009 and Masters et al [2012b], who found that the plasma beta just inside the magnetopause can be of the order 10.…”
Section: 1002/2014ja019774mentioning
confidence: 62%
“…The plasma beta measured by the spacecraft for these crossings ranged between 15 and 25 and was exceptional compared to previous studies by Sergis et al [2007Sergis et al [ , 2009 and Masters et al [2012b], who found that the plasma beta just inside the magnetopause can be of the order 10.…”
Section: 1002/2014ja019774mentioning
confidence: 62%
“…Rhea orbits Saturn at the edge the planet's E-ring (Baum et al, 1981), at location which can be seen as a "transition region" within the magnetosphere: there the magnetic field holds its dipolar configuration to a large extent but the magnetic field magnitude drops to values around 30 nT, while the plasma pressure is almost peaked (Sergis et al, 2007), leading to plasma beta values around unity.…”
Section: Saturn's Moon Rheamentioning
confidence: 99%
“…The inbound magnetospheric leg of the encounter is dominated by the suprathermal and magnetic pressures, the first one being known as, on averaged, the major pressure contribution in the outer magnetosphere (Sergis et al, 2007(Sergis et al, , 2009). The estimated dynamic pressure is of the same order of the magnetic term, whereas the electron thermic pressure is smaller by a factor 10.…”
Section: The Pressure Environmentmentioning
confidence: 99%
“…The last pressure term is given by the energetic particles, deduced from the MIMI CHEMS data (Krimigis et al, 2004) using the method developed by Sergis et al (2007). This suprathermal pressure corresponds to both H + and O + (major plasma components) for energies above 3 keV.…”
Section: The Pressure Environmentmentioning
confidence: 99%
See 1 more Smart Citation